Fluorosis dental en escolares y exploración de factores de riesgo: municipio de Frontino, 2003 - Ramírez-P., Blanca Susana; Franco-C., Ángela María; Sierra-L., Jorge Luis; López-C., Rosa Virginia; Alzate-Y., Teresita; Sarrazola-M., Ángela María; Pimienta-T., Carolina; Morales-R., Carolina (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The purposes of this study were: 1. To determine the prevalence and distribution of dental fluorosis in schoolchildren ages 8-12 and 15 years of age in the town of Frontino-Colombia, 2. To explore the behavior of the risk factors associated with dental fluorosis (fluoride concentration in the water, salt and toothpastes). Dental fluorosis was evaluated in a representative sample of 810 schoolchildren distributed in 4 geographic strata according to the previous knowledge on cases of reported dental fluorosis. The Thylstrup and Fejerskov index (TFI) was used for the classification of clinical findings. The water samples collected (33) from the most recognized sources by urban and rural inhabitants as well as salt samples (38) were analyzed using the direct method, and the toothpaste samples by the microdiffusion method (HDMS). The prevalence of dental fluorosis was 67%, being 1-3 levels the most frequent ones. Fluoride concentrations in all the water samples were under 0.05mg/L. Among the salt samples collected from the town grocery stores and homes, 60.4%, did not comply with the norm on fluoride concentration established in Colombia. The average fluoride concentration in the toothpaste samples was 1504 + 387 ppm. This study concluded that dental fluorosis is explained by the multiple ingestion of fluoride coming from fluoridated table salt and from toothpastes. The recommended strategies are a permanent surveillance of the fluoridated salt program and educating the community and dentists on how to correctly use fluoridated products.